Application of Differentiated Pedagogy to Increase Students Ecoliteracy in Social Studies Learning - Fadlurrahman, Farras; Supriatna, Nana; Ratmaningsih, Neiny (International Journal of Social Service and Research, 2024)
This research aims to increase students' ecoliteracy in social studies learning. So far, not many teachers have implemented environmental-based learning in social studies learning in the classroom. The development of ecoliteracy is in accordance with the mandate of the UU NO 32 of 2009 and Environmental Management. Indicators of ecoliteracy abilities in this research include aspects of knowledge, attitudes and skills. The research location was carried out at SMP Negeri 5 Cimahi (Public Junior High school) which has environmental cleanliness problems. The research method used in this research is classroom action research using the Lewin model design interpreted by Kemmis. In its implementation, which coincides with the implementation of P5, there are 3 (three) cycles with a total of 12 actions, each of the three cycles has a different discussion concentration. The first cycle concentrates on the knowledge aspect with 5 actions, the second cycle concentrates on the attitude aspect with 4 actions, and the third cycle focuses on the skills aspect with 3 actions. As a result of this research, researchers obtained data on increasing aspects of attitudes towards the environment, getting an increase in scores from 1722.5 to 1820.0. Meanwhile, the score for the skills aspect has increased, it can be explained that research by developing ecoliteracy intelligence in social studies learning with a differentiated ecoliteracy approach has shown an increase in students' knowledge, attitudes and ecoliteracy intelligence skills. This shows that differentiated ecoliteracy learning can be a solution in solving problems in the classroom related to environmental problems.